2017
DOI: 10.1038/srep42186
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of platelet TGF-β release in podoplanin-mediated tumour invasion and metastasis

Abstract: The tumour microenvironment is critical for various characteristics of tumour malignancies. Platelets, as part of the tumour microenvironment, are associated with metastasis formation via increasing the rate of tumour embolus formation in microvasculature. However, the mechanisms underlying the ability of tumour cells to acquire invasiveness and extravasate into target organs at the site of embolization remain unclear. In this study, we reported that platelet aggregation-inducing factor podoplanin expressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 49 publications
4
91
1
Order By: Relevance
“…VEGF was one of the most upregulated genes in CNS leukemic cells. Similar findings were recently reported in Blood by Kato et al, 4 who also confirmed the increased expression of VEGF in ALL cells isolated from the CSF of patients with CNS leukemia. These observations complement a previous report of high levels of VEGF in the CSF from patients with CNS leukemia.…”
Section: Shaisupporting
confidence: 79%
See 3 more Smart Citations
“…VEGF was one of the most upregulated genes in CNS leukemic cells. Similar findings were recently reported in Blood by Kato et al, 4 who also confirmed the increased expression of VEGF in ALL cells isolated from the CSF of patients with CNS leukemia. These observations complement a previous report of high levels of VEGF in the CSF from patients with CNS leukemia.…”
Section: Shaisupporting
confidence: 79%
“…6 VEGF may also promote the survival of cancer and leukemic cells. ) and the apoptosis observed by Kato et al in CNS leukemic cells after treatment with bevacizumab, 4 it is likely that VEGF supports the survival of ALL cells in the hypoxic growth inhibitory environment in the subarachnoid compartment. Indeed, this may be its more important function in CNS leukemia.…”
Section: Shaimentioning
confidence: 96%
See 2 more Smart Citations
“…Platelet C-type LECtin-like receptor (CLEC-2/Aggrus) is another platelet receptor that initiates platelet activation through molecular multimerization [66,41,62,67,68]. CLEC-2 binds to mucin glycoprotein podoplanin [6971].…”
Section: Platelet “First Response” Facilitated Clot/wound Biologymentioning
confidence: 99%